Research on the Cities of Pre-Partition Poland in the Last Decade (Trends, Achievements, Perspectives): Bibliographical Survey - Okniński, Piotr (Acta Poloniae Historica, 2023)
The article contains a synthetic review of the most important subjects and directions of research in the field of the history of cities and townspeople in pre-partition Poland (to the end of the eighteenth century) based on scholarly publications from the last ten years. The author characterises the attitude of contemporary historians of cities towards questionnaires and research methods worked out in the second half of the twentieth century in the area of socio-economic history. He also outlines the prospects for the further development of Polish urban historiography, emphasising the importance of taking inspiration from the achievements of cultural anthropology and the cooperation of historians with representatives of other humanistic disciplines.